(untitled) (Bangladesh Journal of Medical Science, 2024)
Introduction: Vitamin D is a fat-soluble vitamin of importance necessary for calcium homeostasis, healthy bones, and prevention of fractures. It has also been linked to many metabolic, infectious and autoimmune diseases. Vitamin D levels are also being studied with respect to oral health issues such as dental caries, and periodontitis. Vitamin D deficiencies have been found to be relatively common among Covid-19 patients and who received supplements experienced less severe symptoms. The credible proposals for vitamin D supplementation to avoid infection and mortality due to Covid-19 validate the chance of raising public awareness on significance of its health benefits. Thus, we carried out this research to study the influence of Covid-19 on Saudi Arabian population’s awareness of vitamin D with a dental public health perspective. Materials and methods: A cross-sectional study of the Saudi Arabian general population was undertaken with 240 subjects, including men and women chosen at random varying a range of age groups from 18 to 74 years after consent and institutional approval. Sample size was computed using G-power software. Pretested, validated questionnaire, translated to Arabic was disseminated through e-mails and all prominent social medias. Statistical analysis was done using statistical package for the social sciences (SPSS) version 26.0. Bivariate analysis was performed using chi-square test at 5% significance level. Results: Out of 240 people participated; 57% were men, and 43% were women. Majority were between the ages of 18 and 30 years. 65% of the participants were aware that vitamin D is important for bone health, supports oral health, reducing tooth decay, and lowering the risk of heart disease. Half of the study population believe that the sunlight is the prime source of vitamin D and 80% assumed that the ideal time of sunshine exposure is in the morning. 88.3% of them projected the need to increase their knowledge about vitamin D. Conclusion: There was a lack of awareness and knowledge about vitamin D and its significance for the body and teeth, as well as its relationship to Covid-19. The pandemic had no significant impact on society’s awareness about vitamin D. This study emphasises the importance of raising awareness among the public about vitamin D and ways to prevent its deficiencies. Bangladesh Journal of Medical Science Vol.23 (Special Issue) 2024 p.S66-S72